Electricity produced using biogas obtained from the recovery of organic waste in ecological landfills – a case study - Sporea, Nicoleta; Durbacă, Ion; Dumitrescu, Anca-Madalina; Tomescu, Gheorghita (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The paper presents an applied technological study regarding the production of biogas and its subsequent use for the production of electricity, at the level of a developed rural agro-zootechnical area.